2014
DOI: 10.1111/brv.12166
|View full text |Cite
|
Sign up to set email alerts
|

Heterothermy in large mammals: inevitable or implemented?

Abstract: Advances in biologging techniques over the past 20 years have allowed for the remote and continuous measurement of body temperatures in free-living mammals. While there is an abundance of literature on heterothermy in small mammals, fewer studies have investigated the daily variability of body core temperature in larger mammals. Here we review measures of heterothermy and the factors that influence heterothermy in large mammals in their natural habitats, focussing on large mammalian herbivores. The mean 24 h b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

9
84
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

6
0

Authors

Journals

citations
Cited by 82 publications
(93 citation statements)
references
References 114 publications
(181 reference statements)
9
84
0
Order By: Relevance
“…Similarly, in hot environments, body core temperature in free-living large mammals, across a broad range of species, varied by less than 2.5°C over 24 h [50,51]. Contrary to what might be predicted from the physical principles of body size, the increase in body core temperature across the day, which is reflected in the amplitude of the 24 h rhythm of body core temperature, is not correlated with the body mass of large free-living mammals with access to drinking water [55]. As shown in Fig.…”
Section: Physiological Adjustmentsmentioning
confidence: 71%
See 4 more Smart Citations
“…Similarly, in hot environments, body core temperature in free-living large mammals, across a broad range of species, varied by less than 2.5°C over 24 h [50,51]. Contrary to what might be predicted from the physical principles of body size, the increase in body core temperature across the day, which is reflected in the amplitude of the 24 h rhythm of body core temperature, is not correlated with the body mass of large free-living mammals with access to drinking water [55]. As shown in Fig.…”
Section: Physiological Adjustmentsmentioning
confidence: 71%
“…In an analysis of body core temperatures obtained from free-living large herbivorous mammals, we found that mean body core temperature decreased by 1.3°C for each 10-fold increase in body mass [55]. However, the relationship between mean body core temperature and body mass also is influenced by phylogeny.…”
Section: Physiological Adjustmentsmentioning
confidence: 83%
See 3 more Smart Citations